TARGETING POLYCYSTIC OVARIAN SYNDROME INFLAMMATION: DOCKING AND PHYTOCHEMICAL PROFILING OF ANTI-INFLAMMATORY COMPOUNDS IN LEONOTIS NEPETIFOLIA - MERLIN MONISHA M; PRAKASH M (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Leonotis nepetifolia is one of the most valuable species in folkloric treatments known to have anti-inflammatory properties devoid of studies on its interventions against polycystic ovarian syndrome (PCOS) - a chronic low-grade inflammatory disorder. This research aims to identify and classify the phytochemicals present in L. nepetifolia using gas chromatography-mass spectrometry (GC-MS). Molecular docking studies were then carried out to analyze their potential binding affinity and interaction with key molecular targets associated with PCOS, offering valuable insights into the fields of natural product pharmacology and women’s healthcare. Methods: The complete phytochemical profiling of methanolic extract of seeds of L. nepetifolia with the aid of GC-MS and the subsequent in silico docking of the anti-inflammatory compounds in L. nepetifolia, against inflammatory markers responsible for PCOS has been carried out. Results: Cis-vaccenic acid and octadecanoic acid were the compounds identified as ligands to be docked against the inflammatory proteins responsible for PCOS. CYP19A1 and AdipoR1 were identified as hit targets with the highest binding scores of −6.4 kcaL/moL and −7.6 kcaL/moL when docked against the ligands, cis-vaccenic acid and octadecanoic acid, respectively. Conclusion: The current study has demonstrated the potential of L. nepetifolia for the development of reliable and effective drugs for treating PCOS. The hit target-ligand interactions can be further investigated for its bio-activities to create new medications. To the best of the authors’ knowledge, this is the first-hand report on phytochemical identification and molecular docking seeking to uncover potential compounds in L. nepetifolia that could alleviate PCOS.